Functionalization of AFM tips for use in force spectroscopy between polymers and model surfaces - Maver, Tina (Materiali in tehnologije, 2011)
The following work presents the use of two different methods for the attachment of different functional groups onto the AFM tip surface. Such functionalized tips then allow for further binding of molecules with different origins and natures, thus allowing for use when measuring forces, and the extent of interactions appearing between two model surfaces and in real systems. Force spectroscopy, in combination with chemical force microscopy (CFM), as used in this study, exhibits great potential for chemical sensing in the field of polymer sciences. In modern wound treatment, it is very important to know the type and ranges of interactions between different polymer materials, which are mostly crucial components of the dressings. Precise measurement of these interactions would help to choose those materials that fit together without the use of additional chemical modifications on their surfaces. Such modifications are often the cause of unpredictable complications during the course of wound healing. This same method could also be used for interaction evaluation between chosen polymer materials with biological macromolecules, which appear within the wound during the healing process. Such in vitro testing could be of great help when optimal wound dressing materials need to be chosen in order to alleviate a patient s suffering after application. Scanning electron and atomic force microscopies were used in order to prove the effectiveness and applicability of the used functionalization procedures.
Keywords: mikroskop na atomsko silo; mikroskop na kemijsko silo; spektroskopija sil; funkcionalizacija konic